Turning hardened steel using coated carbide at high cutting speeds - Aneiro,Federico M. (2008)
The present work studies some aspects of the turning process applied on hardened steel using multilayer coated carbide tools at high cutting speeds. The influence of cutting parameters (vc, f, and depth of cut - d.o.c.) on tool temperature, tool wear, cutting forces, and surface roughness were analyzed. The current literature reports many studies using PcBN on hardened steel, but it is also important to know the results when using coated carbide tools, mainly for economical reasons. Temperature was measured by a thermocouple positioned at the lowest insert face, underneath it. Temperature near the rake face was calculated using the measured gradient within the insert thickness. To measure the gradient a special technique was used with one embedded thermocouple near the rake face and one underneath. Tool wear measurements demonstrated the capability of such tools in turning hardened steel with reasonable tool life. Forces measured resulted in relatively low values, being the radial component the largest of all. For the different cutting conditions studied, the doc has the greatest influence on force and temperature. Additionally, the best surface roughness values were smaller than 0,4 µm Ra.